The Role of German Preverbs in Clausal Selection Properties - Barbara Stiebels (Languages)
One aspect of clausal embedding that has not received any specific attention in the literature is the question of whether and how derivational morphology may affect clausal selection properties of the respective bases. In this paper, I will focus on the role of German preverbs for clausal embedding. I will show that any parameter of clausal embedding can be affected by a preverb, though sometimes in a non-compositional way. Preverbs may affect presuppositions and entailments of their base verb, their selectional behavior with respect to clause types, their status as control or raising predicate and their potential for restructuring. Furthermore, preverbs may license or block neg-raising. The first part of the paper is dedicated to the demonstration of these effects with no specific preverb in mind. The second part discusses three specific preverb patterns with zu- ‘to’, ein- ‘in’ and er-, showing their specific clausal complementation properties. Preverbs influence clausal complementation by their impact on the argument structure/realization (in the case of control and restructuring) and on the lexical aspect of the base (in the case of certain interrogative complements and neg-raising).